Gender Differences in Science and Mathematics Achievement at the Primary Level – A Case Study - KHAN, AIYAZ AHMAD (THE PRIMARY TEACHER, 2014)
Academic achievement depends upon several factors. The present study focuses on gender differences in academic achievement. The aim of the study is to compare the achievement of boys and girls in science and mathematics at the primary level. The sample comprises 110 students (57 boys and 53 girls) from the affiliated schools of Aligarh Muslim University, Aligarh. The data was collected using two self-developed achievement tests. The collected data was analysed with the help of statistical techniques like Mean, SD and ‘t’ value. The findings show that there is significant difference in achievement of boys and girls in science and mathematics at the primary level. The performance of boys is better than their girls in both science and mathematics.